O abismo na política: crise e liberdade a partir do pensamento político de Hannah Arendt - Silva Neto, Joaquim Onofre (2020)
Based on Hannah Arendt, the present proposal intends to work with the theme of crisis and freedom and its relationship with the disbelief that civil society feels for politics. For that, it considers it necessary to discuss, in the Arendtian bibliography, the concepts of freedom and crisis, since this study implies the fundamental importance that both have for the totality of the works of this German thinker. This interpretive objective, outlined earlier, is based on the hypothesis that language is a path through which human beings leave traces of their impressions about the external world, from the first moment that they ventured to interpret this exteriority. Thus, in words, in concepts, the legacy of old meanings remains, which provide the sedimentary basis for the new meanings that come after it. Now, this is precisely the purpose of how the theme of this proposal will be treated philosophically, that is, through a reflection based on an analysis of the old remnants present in the concepts of freedom and crisis, in order to understand if there is something that approach as phenomena of contemporary politics. However, this analysis will not go into depth for all the complexity of this subject, as it is a conceptual cut that will gravitate around the work of Hannah Arendt, specifically in her political theory, both because she is considered a thinker of freedom and rupture and because she also uses the etymological rescue of the concepts she studies as an investigative method. Furthermore, although Arendt uses the word crisis in several of his texts, it is interesting that he does not directly relate it to the concept of freedom, that is, in the work of this thinker, there does not seem to be an explicit idea that involves crisis and freedom together. In this sense, this point of injunction between concepts is the object of analysis that we intend to discuss and understand here. For today, laying the foundations for understanding the closeness between crisis and freedom is relevant due to its possible relationship with the upsurge in social and political conflicts that civil society has been going through, to the point that the resurgence of authoritarian movements - fruits of the collapse of the concept of freedom, of the instability of the public sphere and of the emptying of the meaning of politics. In this case, it is significant to investigate how the concepts of crisis and freedom act in the understanding of totalitarian phenomena, having as an auxiliary scope in the contemporary debate about the damage of political tensions in the current scenario.